The rooster bar (Random House Large Print, Knopf Doubleday Publishing Group, Books on Tape, Doubleday, Random House Audio, 2017)
"Mark, Todd, and Zola came to law school to change the world, to make it a better place. But now, as third-year students, these close friends realize they have been duped. They all borrowed heavily to attend a third-tier, for-profit law school so mediocre that its graduates rarely pass the bar exam, let alone get good jobs. And when they learn that their school is one of a chain owned by a shady New York hedge-fund operator who also happens to own a bank specializing in student loans, the three know they have been caught up in The Great Law School Scam. But maybe there's a way out. Maybe there's a way to escape their crushing debt, expose the bank and the scam, and make a few bucks in the process. But to do so, they would first have to quit school. And leaving law school a few short months before graduation would be completely crazy, right? Well, yes and no"--

Bloody genius (Virgil Flowers novels, 12,, 2019)
"At the local state university, two feuding departments have faced off on the battleground of PC culture. Each carries their views to extremes that may seem absurd, but highly educated people of sound mind and good intentions can reasonably disagree, right? Then someone winds up dead, and Virgil Flowers is brought in to investigate ... and he soon comes to realize he's dealing with people who, on this one particular issue, are functionally crazy. Among this group of wildly impassioned, diametrically opposed zealots lurks a killer, and it will be up to Virgil to sort the murderer from the mere maniacs."--

College admission essentials: a step-by-step guide to showing colleges who you are and what matters to you (Sourcebooks, 2020)
"What if you could take control of the admissions process, as you apply for your dream school, and do it in a way that's both effective and empowering? From filling out your extracurriculars to interviewing with admissions staff, it comes down to two questions: What matters most to you? How does it manifest in your life? The answers to these questions will fuel every aspect of your college admissions experience, and Ethan Sawyer (the College Essay Guy), along with advice from dozens of top admissions experts, will help you stand out against the toughest competition"--

Moo (Alfred A. Knopf, Compass Press, 1995)
A satire on university life, describing the rackets and the intellectual dishonesty that goes on. The setting is the U of Moo where research into the destruction of rain forests is tailored to suit the corporation funding the project. By the author of A Thousand Acres.

Daddy-Long-Legs (Puffin classics, ,, 1985)
A seventeen-year-old orphan is sent to a posh northeastern college for women by an anonymous benefactor. All she must do is write to the man she nicknames Daddy-Long-Legs and tell him of her progress.

Public no more: a new path to excellence for America's public universities (Stanford Business Books, an imprint of Stanford University Press, 2012)
Description Not Provided

Peterson's four-year colleges (Peterson's, 2001)
Description Not Provided

America's best colleges for B students: a college guide for students without straight A's (SuperCollege, LLC, SuperCollege, 2011)
"High school students who get average grades and don't ace the SAT or ACT discover that an exceptional college education is by no means beyond their reach with this guide. Along with information on what to look for in a college and what colleges look for in their students besides grades, this college reference provides details on more than 175 colleges that make it a point to help students who have not achieved a stellar GPA and includes information on whether colleges feature extra tutoring, help from professors, and distance-learning programs. Advice on the application process emphasizes the schools that look beyond GPA to the extracurricular activities and community involvement at which many average students excel. Quelling both students' and parents' fears about finding a good education with a less-than-perfect academic record, this guide makes it clear that it is always possible. This updated edition has new data on student life, financial aid and costs, deadlines, and admissions information"--Amazon.
section 1. Choosing : how to choose the right college for you , section 2. Getting in : beyond the basic application from : explaining weaknesses and building on strengths , section 3. Paying : B students can win scholarships too , section 4. The colleges : a guide to the colleges that welcome B students.

The law of higher education: a comprehensive guide to legal implications of administrative decision making (Jossey-Bass higher and adult education, ,, 2019)
"In the increasingly litigative environment of higher education, this comprehensive, practical, and up-to-date legal guide is indispensable for administrators, attorneys, and researchers. Due to numerous changes in the law and many new cases since the previous edition, the Fifth Edition contains new material relating to: hate speech and free speech rights of faculty in public universities; student suicide; campus safety; police and administrators' right to search students' residence hall rooms; and nondiscrimination and affirmative action in employment, admissions, and financial aid"--
Overview of higher education law , Legal planning and dispute resolution , The college and its trustees and officers , The college and its employees , Nondiscrimination and affirmative action in employment , Faculty employment issues , Faculty academic freedom and freedom of expression , The student-institution relationship , Student Academic Issues , Student Disciplinary Issues , Rights and responsibilities of student organizations and their members , Local governments and the local community , The college and the state government , The college and the federal government , The college and the education associations , The college and the business/industrial community.

Accreditation: a struggle over standards in higher education (Harper, 1960)
Description Not Provided

Becoming beholders: cultivating sacramental imagination and actions in college classrooms (Liturgical Press, 2014)
Description Not Provided

Ustav slavistiky: vychodiska a perspektivy (MUNI arts 100, ,, 2019)
Description Not Provided

A new kid on the block: the University of South Australia in the Unified National System (Melbourne University Press, 2016)
Description Not Provided

Het Einde van de Universiteit (volgens een rapport van de Universiteit van Oeloemia) (Vossiuspers UvA, 2007)
Description Not Provided

Německá vysoká škola technická v Praze (1938-1945): struktura, správa, lidé (Univerzita Karlova, 2017)
Description Not Provided

Cesko-madarske ob(z)ory: Kapitoly z dejin cesko-madarskych univerzitnich vztahu (Univerzita Karlova, 2018)
Description Not Provided

Invitational education and practice in higher education: an international perspective (Lexington Books, 2016)
Description Not Provided

Integrated resource and budget planning at colleges and universities (Society for College and University Planning, 2011)
Description Not Provided

Under pressure: higher education institutions coping with multiple challenges (Higher Education Research in the 21st Century, Volume 11,, 2019)
Description Not Provided

Il nuovo sistema contabile e di bilancio delle università: caratteristiche e criticità (G. Giappichelli Editore, 2012)
Description Not Provided